IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF PROBLEM-BASED LEARNING APPROACH IN ELEMENTARY SCHOOL PEKANBARU - Fajar Hamzah (UIR PRESS, 2024)
Students' low interest in learning creates challenges in the learning process, where a lack of motivation reduces students' active participation in teaching and learning activities. Therefore, it is essential to identify strategies that can increase students' interest in learning so that they are enthusiastic about participating in learning. This research aims to overcome the low learning outcomes of the Theme 1 Subtheme